Adaptive Equipment-Based Learning to Improve Backhand Stroke Skill Acquisition in Secondary School Table Tennis - Nurul Annisa; Najwa Alia Jahra Harefa; Abdillah Ramadhan; Dianli Simamora (Joska: Jurnal Isori Kampar, 2026)
Purpose: This study aimed to investigate the effect of a systematically structured adaptive equipment-based learning (AEL) protocol on backhand stroke skill acquisition among Grade VIII junior high school students. Materials and Methods: A quasi-experimental pre-test/post-test control-group design was employed with 60 participants (Mage = 13.7 ± 0.5 years; 30 male, 30 female) from SMP Negeri 1 Tebing Tinggi, North Sumatra, Indonesia, randomly allocated to an experimental group (AEL protocol, n = 30) and a control group (conventional instruction, n = 30). Both groups completed 16 instructional sessions over eight weeks. Backhand stroke proficiency was quantified using a validated stroke-accuracy rubric and a ball-placement consistency index. Between- and within-group differences were examined via paired-samples t-tests, independent-samples t-tests, and Cohen's d effect sizes at α = .05. Results: The experimental group demonstrated significantly greater improvement in stroke-accuracy scores (pre: 52.4 ± 6.1; post: 74.8 ± 5.3; p < .001; d = 3.81) compared with the control group (pre: 51.9 ± 5.8; post: 60.3 ± 6.0; p < .001; d = 1.41). Between-group post-test differences were statistically and practically significant (p < .001; d = 2.54). Conclusions: AEL meaningfully accelerates backhand stroke skill acquisition relative to conventional instruction. These findings support the integration of evidence-based equipment modification principles into secondary school physical education curricula.